Karakterisasi Bakteri Penyebab Busuk Lunak pada Umbi Porang (Amorphophallus muelleri) Menggunakan Primer PCR Spesifik - Ely Lailatul Maghfiroh; Abdul Munif; Abdjad Asih Nawangsih; Alina Akhdiya (Jurnal Ilmu Pertanian Indonesia, 2022)
Porang is one of the export commodities whose production is currently intensive by the Indonesian Government. Soft rot disease is one of the obstacles in cultivation and post-harvest of porang, which results in a decrease in productivity and quality of porang. This study aims to isolate pathogenic bacteria that infect porang tubers and determine their morphological and molecular characters. A total of 43 bacteria were isolated from porang tubers with soft rot symptoms from Malang Regency. Ten isolates of them showed positive reactions in the hypersensitivity test. Amylolytic, pectinolytic, mannanase, and proteolytic activities were shown by three bacterial isolates, including B4, B7, and BLUB15, by forming a clear zone around the inoculation point. The results of the decay test showed that B4 isolate had the most severe signs of decay, up to 97.88% in potato tubers and 37.12% in the porang frog. A pair of ExpccR/ExpccF PCR primers successfully detected B4 isolate as Pectobacterium carotovorum subsp. carotovorum (Pcc) in the 550 bp band. Unexpectedly, identifying the other two isolates did not show any similarity to the bacteria that cause soft rot, which was previously known. The two isolates showed similarities to Empedobacter sp. B7 (98.7%) and Pseudomonas sp. BLUB15 (97.6%) as a result of 16S rRNA gene analysis. So far, based on the existing literature, this is the first report of phytopathogenic bacteria causing soft rot outside the genus Pectobacterium and Dickeya. Keywords: decay, glucomannan, mannanase enzyme, pectobacterium